1997
DOI: 10.1056/nejm199701233360404
|View full text |Cite
|
Sign up to set email alerts
|

Neurodevelopment of Children Exposed in Utero to Antidepressant Drugs

Abstract: In utero exposure to either tricyclic antidepressant drugs or fluoxetine does not affect global IQ, language development, or behavioral development in preschool children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
155
0
4

Year Published

2003
2003
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 508 publications
(164 citation statements)
references
References 21 publications
5
155
0
4
Order By: Relevance
“…In line with previous studies (Klinger et al 2011;Nulman et al 2012;Nulman et al 1997;Nulman et al 2002), we found no significant difference in performance between the three groups of children in terms of general cognitive abilities as tested by the WPPSI-r. Further, regarding more specific aspects of inhibition, we found no association between prenatal exposure and performance on the two NEPSY-II tasks. Preliminary analysis of the ANT paradigm indicated that the desired conflict effect was elicited in all three groups, supporting the notion that this task is an appropriate measure of interference suppression in young age groups.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In line with previous studies (Klinger et al 2011;Nulman et al 2012;Nulman et al 1997;Nulman et al 2002), we found no significant difference in performance between the three groups of children in terms of general cognitive abilities as tested by the WPPSI-r. Further, regarding more specific aspects of inhibition, we found no association between prenatal exposure and performance on the two NEPSY-II tasks. Preliminary analysis of the ANT paradigm indicated that the desired conflict effect was elicited in all three groups, supporting the notion that this task is an appropriate measure of interference suppression in young age groups.…”
Section: Discussionsupporting
confidence: 92%
“…As suggested by recent literature on child cognitive development in an atypical environment such as maltreatment (Augusti and Melinder 2013) and prenatal methadone exposure (Konijnenberg and Melinder 2013), there are limited associations between early life stress and global deficits of cognition. Furthermore, among the previous studies, the age range is fairly broad (e.g., 2-7-year-olds), complicating the task of comparing across age groups and neurocognitive tests (Klinger and Merlob 2008;Nulman et al 2012;Nulman et al 1997;Nulman et al 2002).…”
Section: Child Development and Maternal Depression: Cognitive And Behmentioning
confidence: 99%
“…Two groups (Nulman et al 1997(Nulman et al , 2002Oberlander et al 2005) have reported normal motor developmental outcomes and one study noted advanced motor development (DiPietro et al 2006) in children with gestational exposure to SSRIs compared to children of healthy controls. Psychomotor delay after in utero SSRI exposure has been recorded before by Simon et al (2002) and has been reported by Casper et al (2003).…”
Section: Discussionmentioning
confidence: 99%
“…In newborns, maternal use of SSRI medication, especially during the last trimester, has been linked to an increased risk of persistent pulmonary hypertension (Chambers et al 2006), premature births (Simon et al 2002;Suri et al 2007;Toh et al 2009;Wisner et al 2009), and alterations in regulatory processes reflected in changes in arousal, rapid eye movement sleep, and pain responses (Laine et al 2003;Oberlander et al 2002;Zeskind and Stephens 2004). Studies on the neurodevelopment of children exposed prenatally to SSRIs have shown variable results, from normal mental and psychomotor development (Misri et al 2006;Nulman et al 1997;Oberlander et al 2005) to evidence for a slight delay in motor development (Casper et al 2003;Mattson et al 2004;Mortensen et al 2003;Pedersen et al 2010). So far, surprisingly little has been published as to whether length of gestational drug exposure bears on birth outcome.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have found that fine-motor skills may be impaired in SSRI-exposed children (21), but no impact on cognitive development has been observed (22,23). However, these studies have In the elevated plus-maze, the total number of entries into either arm was recorded.…”
mentioning
confidence: 97%